Computers: their history and how they work, - Rusch, Richard B. (Simon & Schuster, 1969)
An introduction to computers which traces their history from the abacus to the modern digital computer, explains how various computers work, defines the special terminology connected with them, discusses their importance in the modern world, and outlines career opportunities in the computer field.